MUSLIM FAMILY LAW REFORM IN INDONESIA (A Progressive Interpretation of The Qurâan) - Mulia, Siti Musdah (Islamic University of Indonesia, 2015)
If we look at Muslim Family laws in different countries or communities, we can see how different they are from one another and how more or less option-giving they are for women. There is obviously no such thing as the Sharia as a God given law, eternal and a-historical. The fact is there are many different Muslim Family laws and they are really man-made. One of the subtle but most pervasive areas of discrimination against women in the Muslim world today is the inequality that occurs within the context of the family. Throughout Muslim countries, Muslim women are speaking out about such discrimination and are fighting for reform of family laws to promote justice and equality within the family. This Article outlines key discriminatory provisions within Muslim Family Law in Indonesia which is called The Compilation of Islamic Law (1991) and the efforts being made by progress Indonesian Muslim to advocate for comprehensive reform of the Compilation. This effort includes developing an understanding of why and how reform of Muslim family laws is possible using the principle of justice and equality in Islamic perspective. The last part of this article will introduce a new draft of The Compilation of Islamic Law which is called the Counter Legal Draft of The Compilation of Islamic Law (The CLD) in 2004, that is based on the principle that the Quranic ideal for the Muslim family is founded on the fundamental Islamic values of human equality and freedom. The CLD is constructed on the premise that the realization of the Quranic vision of the family can be achieved only if the values of equality and freedom are reflected in all aspects of the regulation of marriage and family. Keywords : Family Law, Reform, Indonesia, CLD KHI and Progressive.